2022
DOI: 10.3390/atmos13101718
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sea Surface Temperature on Relative Humidity and Atmospheric Visibility of a Winter Sea Fog Event over the Yellow-Bohai Sea

Abstract: Sea fog is one of the main types of dangerous weather affecting offshore operations. The sea surface temperature (SST) has an important influence on the water vapor content and intensity of sea fog. In order to study the impact of SST on local relative humidity and atmospheric visibility, a sea fog episode that occurred over the Yellow Sea and Bohai Sea on 21 January 2013 was investigated through observational data, reanalysis data, and Weather Research and Forecasting (WRF) simulation. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We estimated fog thickness based on sounding data and found that average CF thickness is larger than EF thickness, which is consistent with ERA5 data (Figure 12c). Abundant studies have analyzed the formation process and characteristics of fog over the YS based on satellite, buoy and ship observation data [10,15,16], but few studies have focused on coastal fog mechanisms. This study found that there are significant differences in the EF and CF characteristics at Liuting International Airport (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated fog thickness based on sounding data and found that average CF thickness is larger than EF thickness, which is consistent with ERA5 data (Figure 12c). Abundant studies have analyzed the formation process and characteristics of fog over the YS based on satellite, buoy and ship observation data [10,15,16], but few studies have focused on coastal fog mechanisms. This study found that there are significant differences in the EF and CF characteristics at Liuting International Airport (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that fog formation over the YS is affected by sea-atmosphere interactions, and the local SST is one of the main driving factors [10,15]. Due to Liuting International Airport's location in the coastal area of Qingdao city, sea-land-atmosphere interactions can influence EF and CF formation, and local SST must be a driving factor for coastal fog formation.…”
Section: Formation Mechanism and Diurnal Variation Of Fogmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the modern Arctic Ocean and NW Pacific Ocean are very different environments (Figure 1 and Figure S4 in Supporting Information S1). From 1982 to 2017, sea surface temperatures (SSTs) in the YS ranged from 13 to 18°C (Y. G. Liu, 2017), and based on older records dating from January 1958 to December 2008, the monthly mean temperatures of bottom waters in the YS were ∼0-10°C between December and May and ∼10-25°C from June to November (Li et al, 2015). Additionally, the mean SST of the Sea of Japan ranged from 5 to 20°C from 1982 to 2018 (Lee & Park, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When the air temperature is higher than the SST, the heat is transported from the air to the sea surface to cool the air, which is conducive to the formation of sea fog [1]. However, if the air temperature is far greater than the SST, and the air in the lower boundary layer is overly stable, the fog will only occur in the near sea surface layer and will not develop upward to reach a greater thickness [10]. Hence, an appropriate air-sea temperature difference play decisive role in the formation of sea fog.…”
Section: Stability Of Air-sea Interfacementioning
confidence: 99%